SamÃ¢â dalam Tradisi Tasawuf - Siradj, Said Aqil (Program Pascasarjana UIN Sunan Ampel Surabaya, 2013)
SamÃ¢â in Tasawuf has been a very important element in the dissemination of this spiritual dimension of Islam. Yet, it has received very little both from the practitioners of Tasawuf and its intellectuals. This paper tries to expose this simply in a hope to make it heard in the academic and popular circle. Here, samÃ¢â is not only understood as a form of music, as many would do, but also as an art of listening of which music is certainly part. The paper will explore the meaning and definition of this term, putting emphasis on its many-faceted function in the formation and development of oneâs soul and spirituality. It is argued that soul is musical and artistic. Using art and music to talk to soul is therefore the proper way and means. The paper will also try to show that samÃ¢â is also an indispensable part of spiritual method to reach and know God. Knowledge of God in other words, can be gained through this practice. Hence, samÃ¢â is treated not only as a form of entertainment, but also a kind of practical epistemology.